Adaptation and validation the integration scale for Indonesian university students: academic and social - Ike Dwiastuti; Wiwin Hendriani; Fitri Andriani (Institute of Advanced Engineering and Science, 2024)
Student integration is a student’s ability to integrate into the social and academic systems of the university. Integration of students has been shown to affect how well they do on campus, which helps them finish higher education. The integration scale (IS) measures integration ability that meets the principle of simplicity. The integration scale is formed of 16 items divided into five aspects and two factors. This study aimed to adapt and validate IS instruments for the Indonesian university student population. The research methods complied with the six-step procedures the International Test Commission set out. A total of 309 participants were undergraduate students. They were between 17 and 23 years old (mean=19.42, SD=1.11 years), with 247 females (79.94%) and 62 males (20.06%). The results of the confirmatory factor analysis revealed that a total of 16 items were valid and reliable. Three models that have acceptable fits were confirmed. The results demonstrate that the Indonesian integration scale measures undergraduate student integration with comparable precision to the original scale. This scale can identify students who require academic and social integration assistance and evaluate the institution’s role in academic development.